The digital transformation at organizations: the case of retail sector - Ferreira, Maria João (2020)
Digital transformation has changed the way we do business in all industries, from health to education. In this scenario, the retail sector is no exception. It is continually affected by advances in digital technologies, which contribute to significant, sometimes drastic and/or disruptive changes in the competitive landscape. Retail is now increasingly digital as multi-sided marketplaces are bringing the online and offline markets together to create better shopping experiences for consumers. In this context, consumers expect to find technology-enriched retail environments. Retailers are looking for advantages, e.g. to grow and create new market opportunities by using technological tools, creating new business models, optimizing and modernizing their practices in a consumer-centric approach. The research presented aims to provide an overview of the critical areas of the sector, perform a trend analysis of the key technologies used and contribute to the prediction of future retail trends.